2014
DOI: 10.1038/mp.2014.5
|View full text |Cite
|
Sign up to set email alerts
|

Stress and corticosterone increase the readily releasable pool of glutamate vesicles in synaptic terminals of prefrontal and frontal cortex

Abstract: Stress and glucocorticoids alter glutamatergic transmission, and the outcome of stress may range from plasticity enhancing effects to noxious, maladaptive changes. We have previously demonstrated that acute stress rapidly increases glutamate release in prefrontal and frontal cortex via glucocorticoid receptor and accumulation of presynaptic SNARE complex. Here we compared the ex vivo effects of acute stress on glutamate release with those of in vitro application of corticosterone, to analyze whether acute effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
88
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(100 citation statements)
references
References 53 publications
11
88
0
1
Order By: Relevance
“…Another form of presynaptic priming is likely associated with the modulation of vesicular release: recent studies reported that stress and (pre)frontocortical GcR activation increase the readily releasable pool of glutamate (Popoli et al, 2011;Treccani et al, 2014). Notably, this form of plasticity requires additional signals coincident with glucocorticoids in the living animal, because in the above study, acute stress ex vivo could increase the depolarizationinduced release of glutamate in the rat (pre)frontal cortex, but the in vitro application of the stress hormone corticosterone was not sufficient alone to achieve the same result (Treccani et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another form of presynaptic priming is likely associated with the modulation of vesicular release: recent studies reported that stress and (pre)frontocortical GcR activation increase the readily releasable pool of glutamate (Popoli et al, 2011;Treccani et al, 2014). Notably, this form of plasticity requires additional signals coincident with glucocorticoids in the living animal, because in the above study, acute stress ex vivo could increase the depolarizationinduced release of glutamate in the rat (pre)frontal cortex, but the in vitro application of the stress hormone corticosterone was not sufficient alone to achieve the same result (Treccani et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, corticosterone applied in vitro onto isolated nerve terminals (synaptosomes) does not affect glutamate release per se (Treccani et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In T cells, GR has a close physical and functional interaction with the T cell receptor (TCR) complex, and GR activation causes a rapid dissolution of TCR-linked GR complexes and inhibits Lck and Fyn, kinases immediately downstream of the TCR [ 52 ]. In neurons of the prefrontal and frontal cortex, GR is present in synaptosomes, as well as in presynaptic membranes and postsynaptic spines, and its activation increases the readily releasable pool of glutamate vesicles in synaptic terminals [ 95 ].…”
Section: Nongenomic Effectsmentioning
confidence: 99%
“…Previous studies that reported differential functions between subregions of the mPFC suggested that the IL is more involved in extinction than in the expression of aversive memory Maroun 2013). The differential participation of the IL and PrL in memory processes has been attributed to the specificity of projection pathways from each cortical region Hoover and Vertes 2007), although little is known about the complex neuronal network functioning of these areas or how these networks interact during stressful situations (van Aerde et al 2008). Considering the amygdaloid nuclei, although IL projects directly to inhibitory intercalated cell masses and the lateral division of the central nucleus of the amygdala to regulate the process of extinction, the main projection target of the PrL is the basolateral nucleus of the amygdala SotresBayon and Quirk 2010), suggesting different roles of each region in limbic-cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…O glutamato é o principal neurotransmissor excitatório no cérebro de mamíferos, mais da metade dos neurônios no cérebro, incluindo todos os neurônios corticais piramidais, utilizam o glutamato como principal neurotransmissor (NIEUWENHUYS, 1994 . Nessa direção, diversos estudos sugerem que a rápida ativação de receptores para corticosterona possa influenciar a neurotransmissão glutamatérgica TRECCANI et al, 2014). Entretanto, ainda não está totalmente claro como os glicocorticóides influenciam a atividade do CPFm e como seus efeitos estão relacionados aos mecanismos de neurotransmissão glutamatérgica na expressão do medo condicionado.…”
Section: Sistema Glutamatérgicounclassified